NOTE ON THE DESIGN OF TWO ROSS TYPE PHOTOGRAPHIC OBJECTIVES - MALACARA HERNANDEZ, D; CORNEJO, AURELIO; CASTRO, JESUS (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1970)
A Ross type photographic objective was designed in order to examine and measure the line deflection in the vicinity of a gravitational field as predicted by Einstein. This objective is of 30 focal ratio, its diameter is 12.5 cm and it covers a 4 degree fi
BOL OBS TONAN TACUB
Keywords: NOTE, DESIGN, TWO ROSS, TYPE, PHOTOGRAPHIC, OBJECTIVES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS